Note on the Coordination of Periodic Processes in Transportation Systems - Cerny, Jan; Mojzis, Vlastislav (Communications - Scientific letters of the University of Zilina, 2005)
The article deals with a coordination of periodic processes in transport systems. It introduces some basic mathematical models useful in process optimization. It also shows some examples of everyday transport practices where this optimization can be used.